2023
DOI: 10.3390/app13021163
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Emotional Empathy in Intelligent Agents to Facilitate Precise Social Interaction

Abstract: The research area falls under the umbrella of affective computing and seeks to introduce intelligent agents by simulating emotions artificially and encouraging empathetic behavior in them, to foster emotional empathy in intelligent agents with the overarching objective of improving their autonomy. Raising the emotional empathy of intelligent agents to boost their autonomic behavior can increase their independence and adaptability in a socially dynamic context. As emotional intelligence is a subset of social in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Emotion recognition has gained a lot of attention recently ( Liao et al, 2022 ) due to its various applications in robotics, education, and human–computer interaction ( Alanazi et al, 2023 ). Previous studies ( Zhao et al, 2021 ; Mamieva et al, 2023 ) have focused on different human modalities, such as voice, writing, facial expressions, and physiological indicators to recognize emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion recognition has gained a lot of attention recently ( Liao et al, 2022 ) due to its various applications in robotics, education, and human–computer interaction ( Alanazi et al, 2023 ). Previous studies ( Zhao et al, 2021 ; Mamieva et al, 2023 ) have focused on different human modalities, such as voice, writing, facial expressions, and physiological indicators to recognize emotions.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that participants step back and think about why I am responding to the situation in that way while residents did eat more, stay away from the workplace and show aggression is alarming in my study. 24 All felt depressed in an emergency. Sharing with family and colleagues was the most relieved and satisfactory method for residents.…”
Section: Discussionmentioning
confidence: 99%
“…The individual's internal emotional state becomes more discernible through personal experiences, physiological conditions, and environmental stimuli. Hence, valuable insights into a person's emotional state can be gleaned through the utilization of emotion recognition techniques [5,6]. Particularly within the realm of humancomputer interaction, the detection of individuals' emotional states assumes tremendous significance [7].…”
Section: A Backgroundmentioning
confidence: 99%